Surgical Outcome of Corrosive Induced Antropyloric strictures - Iqbal, Asif; Talat, Nabila; Liaqat, Naeem; Hashim, Imran; Haider, Naveed; Saleem, Muhammad; Rasheed, Gohar (Iranian Journal of Pediatric Surgery, 2020)
Introduction: Corrosive induced upper gastrointestinal tract injuries in pediatric patients, is not easy to treat. Interestingly only few reports are available in English literature highlighting the management and surgical outcome of corrosive induced antropyloric strictures. The aim of this study was to determine the presenting features, management and outcome of patients treated at our institute with corrosive induced antropyloric strictures. Methods: This retrospective descriptive study was conducted at Paediatric Surgery Department of Children Hospital & Institute of Child Health, Lahore. Medical records of patients admitted for corrosive-induced gastric out let obstruction from January 2013 to December 2018 were included. The demographic, preoperative assessment, investigations, surgical procedure and follow up details were noted in a proforma. Results were analyzed by descriptive statistics using SPSS version 20. The quantitative variables were presented as mean ± SD. Qualitative variables were presented as frequency and percentages. Results: A total of 62 patients were included in this study. The mean age at presentation was 4.9 ±3.9 years. Of these 67.7% were male and the mean weight of children at the time of surgery was 12.6 ± 5.0 kilo grams. Bathroom cleaner was ingested by 77.4%. Vomiting was seen 100% cases while abdominal pain and weight loss was seen in 38.7 %, and 80.6% respectively. We preformed Heinke-mikulicz pyloroplasty in 59(95.2%) patients, Billroth II in 1(1.6%) and gastrojejunostomy in 2(3.2) cases. Postoperatively 40 children remained well during early post- op period while leak and respiratory issue were seen in 11.9% and 13.6% patients respectively. The mean hospital stay was 27.9±11.5 days. Two patients died after surgery and the rest were discharged. Mean fallow up 15.2±70 months. Of 60 discharged children 37 (62.7%) had no issue while 4 (6.8%) had leakage from previous jejunostomy site leak other 19 patients were lost to follow up. Conclusion:We conclude that surgical treatment for Antropyloric strictures due to corrosive injuries is an acceptable option with minimal complications. However, we emphasize on the preventive measure, child-proof containers and legislations to be taken by authorities and social welfare societies